The Peopleʼs Republic of Chinaʼs Growing Presence in the Middle East in te 21st Century - Wierzejski, Eryk (Vade Nobiscum, tom XXIV/2024: Studia nad Bliskim Wschodem, 2024)
As a country aspiring to become a leading superpower in the multilateral world, the People’s Republic of China is intensifying its international presence in every region of the world. Xi Jinpingʼs coming to power ends the era of Deng Xiaopingʼs 28-character doctrine of „hiding its own capabilities”. The change in power begins the era of the Chinese Dream, which is expected to result in a great Chinese renaissance by 2049. The reborn is to be a state that determines international politics. The Middle East region has become a key area in PRC policy over the past decades. The region is important to Beijing because of its raw materials (oil imports) and its strategic location at the junction of three continents (Europe, Africa and Asia). The strategic aspect manifests itself in aspects of China’s economic, political and military presence tasked with securing Chinese interests in the region. The purpose of this article is to analyze selected aspects of the Chinese presence in the Middle East in the 21st century. Economic, political and military aspects of the Middle Kingdomʼs increasing presence in the region are analyzed. Also analyzed is the aspect of the desire of the government in Beijing to displace the American sphere of influence. The hypothesis of the article is that the Peopleʼs Republic of China is systematically increasing its involvement and influence in the Middle East, while balancing between competing with the United States and being a beneficiary of the US presence in the region.